2017
DOI: 10.2147/ijgm.s140197
|View full text |Cite
|
Sign up to set email alerts
|

A pilot evaluation of a computer-based psychometric test battery designed to detect impairment in patients with cirrhosis

Abstract: BackgroundPsychometric testing is used to identify patients with cirrhosis who have developed hepatic encephalopathy (HE). Most batteries consist of a series of paper-and-pencil tests, which are cumbersome for most clinicians. A modern, easy-to-use, computer-based battery would be a helpful clinical tool, given that in its minimal form, HE has an impact on both patients’ quality of life and the ability to drive and operate machinery (with societal consequences).AimWe compared the Cogstate™ computer battery tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, we found a negative correlation between brain activity in the left ACC and the complete time of NCT‐A, a neuropsychological test measuring concentration, mental tracking, and audio‐visuomotor functions (Cook et al., 2017). This finding indicates that brain activity abnormalities in the left ACC can reflect neurobehavioral deficits in LC patients.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, we found a negative correlation between brain activity in the left ACC and the complete time of NCT‐A, a neuropsychological test measuring concentration, mental tracking, and audio‐visuomotor functions (Cook et al., 2017). This finding indicates that brain activity abnormalities in the left ACC can reflect neurobehavioral deficits in LC patients.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, we found a negative correlation between brain activity in the left ACC and the complete time of NCT-A, a neuropsychological test measuring concentration, mental tracking, and audio-visuomotor functions (Cook et al, 2017 has revealed that aberrant brain activity at resting state may be involved in neurocognitive impairments in low-grade HE patients, through measuring cerebral glucose metabolism by PET (Lockwood et al, 2002). Thus, our meta-analysis might provide reliable imaging biomarker for a better understanding of the pathophysiological mechanisms of HE, and provide potential therapeutic targets.…”
Section: Decreased Brain Activity In Hementioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, our further partial correlation analysis results of the CI group also support these findings partially, which revealed that the completion time of TMT‐A was negatively correlated with nodal degree in the left PCG, and SDMT scores were positively related to nodal efficiency in the bilateral SFGmed and right PCUN. Notably, TMT‐A and SDMT are neuropsychological tests that evaluate cognitive domains in concentration, mental tracking, visuomotor speed, psychomotor speed, attention, and visual memory (Cook et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The digit symbol substitution test (DSST) [31] is a cognitive tool introduced as a paper-and-pencil test originally applied in order to understand human associative learning. Currently, this test is commonly applied in clinical neuropsychology to measure cognitive dysfunction and is often present in cognitive and neuropsychological test batteries [32,33]. The DSST allows one to check the patient's processing speed, memory, and executive functioning [34].…”
Section: Introductionmentioning
confidence: 99%